A transdisciplinary framework for SLA: essential understandings for L2 researchers and teachers - Hall, Joan Kelly (Penerbit Universiti Kebangsaan Malaysia, 2018)
The transdisciplinary framework, initially proposed by the Douglas Fir Group (2016) and elaborated upon in Essentials of SLA for L2 Teachers (Hall, 2019), is new intellectual structure for understanding the many dimensions of learning additional languagesi . In this paper, I first overview the framework, and then lay out eight fundamental themes on language and learning that derive from the framework and offer action possibilities for research. Finally, I offer six implications arising from the themes for L2 teaching.